Relegious Counselors Efforts in Shaping the Positive Character of Adolescents Who Drop Out of School in Sei Bilah Pangkalan Brandan - sabrina, sabrina; Akbar, Ali (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Religious instructors are the â€œspearheadâ€ of the Ministry of Religion in carrying out the duties and functions of fostering religious communities in order to improve the quality of people's religious life. This study aims to explore the efforts of religious instructors in shaping positive character in adolescents who drop out of school in Sei Bilah Village, Pangkalan Brandan. In the context of this community, teenagers who drop out of school often fall into promiscuity, so the role of religious instructors as pioneers assigned to deal with this problem is important. This research uses a qualitative approach by analyzing data using the Miles and Huberman method which includes data reduction, data presentation, conclusion drawing, and triangulation. Through regular coaching every week, religious instructors provide guidance, advice, as well as effective strategies to form positive characters in teenage dropouts. The methods used include mentoring and Quran literacy training to eradicate Quran illiteracy. The findings from this study are expected to provide valuable insights in improving the coaching of out-of-school youth at the local level and contribute to the development of better practices and policies in the future.